Following the footsteps of Dr. Rodolfo Lenz. Dialogues in Pehuenche dialect, spoken in the Alto Bío-Bío (VIII Region) - Sánchez C., Gilberto (Boletín de Filología, 2023)
The article makes known the Mapudungun versión of dialogues colected by Dr. Rodolfo Lenz, which were included in his book Estudios Araucanos. The dialogues are exactly as they are expressed today in Chedungun, the dialectal variant of the language spoken in the Pehuenche community of Cauñicú, in the Alto Bío-Bío (VIII Region). These dialogues were shared by various speakers who are highly competent in their natal tongue. The dialogues in Chilean Pehuenche obtained by Dr. Lenz fron Sejundo Jara (Kallvün) are included for comparativwe purposes.